Loan Guarantees in a Democracy - Papageorgiou, Stylianos; Ziros, Nicholas (The Review of Corporate Finance Studies, 2025)
Abstract We study the political economy of loan guarantees within a credit-rationing framework. A government uses guarantees to decrease the borrowing cost, thus making more households incentive compatible. This shifts capital to productive projects (allocative effect). Backed by taxpayers, loan guarantees also shift consumption from nonborrowers to borrowers (redistributive effect). While a welfare-maximizing planner is only concerned about the allocative effect, vote-share-maximizing politicians are driven by the interaction of both effects. As a result, politicians may underprovide or overprovide guarantees compared to the welfare-maximizing solution, depending on the electoral setup, household risk aversion, income heterogeneity, and guarantees’ externalities. (JEL D72, G28)